The David Foster Wallace Reader - Wallace, David Foster (Little, Brown and Company, 2014)
"Wallace's explorations of morality, self-consciousness, addiction, sports, love, and the many other subjects that occupied him are represented here in both fiction and nonfiction. Collected for the first time are Wallace's first published story, "The View from Planet Trillaphon as Seen In Relation to the Bad Thing" and a selection of his work as a writing instructor, including reading lists, grammar guides, and general guidelines for his students. A dozen writers and critics, including Hari Kunzru, Anne Fadiman, and Nam Le, add afterwords to favorite pieces..."--